MODELING AND STATISTICAL VARIATIONS OF LONG TERM OF MECHANICAL PROPERTIES OF CONCRETE MODIFIED WITH WASTE STEEL SLAG - NOORI, GONA I.; FAQEMAHMOOD, LINA A.; MOHAMMED, SARKAN S.; SALIH, AHMED (Journal of Duhok University, 2020)
This study aims to evaluate and quantify the effect of steel slag (s), water-cement ratio (w/c), and curing time (t) together on the compressive and tensile strengths of concrete. In this research, the results were supported by more than 200 data collected from different research studies. The various water-cement ratio used between 0.32 - 0.70 with a different steel slag percent up to 100% as a complete replacement of fine aggregate (sand), and up to 90 days of curing time was considered. The strengths range of modified concrete up to 36% replacement of compressive and tensile strengths were between 10-70 MPa and 2-7 MPa respectively, and strengths of conventional concrete were between 10-62 MPa and 2-6 MPa respectively. Concrete Mechanical properties with the use of steel slag, different range of w/c, and curing time were correlated using different numerical models which show that both predicted and experimented mechanical properties of conventional and modified concrete with steel slag are close to each other referring to the coefficient of determination (R²) and root mean square error (RMSE). Compressive (σc) and tensile (σt) strength of concrete as a function of w/c, curing time, and steel slag using the Non-Linear Model (NLM) resulted properly.